PERFORMANCE OF THE FMA+ FOREST FIRE HAZARD INDEX FOR THE SERRA DO TOMBADOR NATURAL RESERVE, GOIÁS, BRAZIL - Freire Almeida, Diego; Kovalsyki, Bruna; Moura Fonseca Lucas, Fernanda; Labres dos Santos, João Francisco; França Tetto, Alexandre (Floresta, 2022)
The aim of this work was to evaluate the performance of the FMA+ fire index for the Serra do Tombador Natural Reserve region in Cavalcante, Goiás. The dataset was composed of records provided by the reserve’s meteorological station and hotspot detection by satellites. The period analyzed was from 2016 to 2020. The index was fitted by modifying the limits of the fire hazard classes of the FMA+, where: a) the distribution of the number of days in each class presented decreasing behavior; and b) the number of days with hotspots by hazard class presented increasing behavior. The performance was evaluated through the skill score and accuracy methods. The FMA+ index received a skill score of 0.5 and accuracy of 75%, but it was necessary to adjust the classes to reach those levels. The results indicated that the adjusted FMA + index was suitable for use in the study region.